2007
DOI: 10.1016/j.biopsycho.2006.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The polyvagal perspective

Abstract: The polyvagal theory introduced a new perspective relating autonomic function to behavior, that included an appreciation of the autonomic nervous system as a "system," the identification of neural circuits involved in the regulation of autonomic state, and an interpretation of autonomic reactivity as adaptive within the context of the phylogeny of the vertebrate autonomic nervous system. The paper has two objectives: first, to provide an explicit statement of the theory; and second, to introduce the features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

165
3,380
16
53

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,736 publications
(3,614 citation statements)
references
References 122 publications
165
3,380
16
53
Order By: Relevance
“…The scores for the total scale (M) and the subscales speech/language/communication (Com), sociability (Soc), sensory and cognitive awareness (Cog) and health/physical/behavior (Beh) are displayed for the preand posttest for Groups 1 and 2. The lower scores in the postcompared to the pre-test indicate treatment success the autonomic nervous system and social cognition is closely linked in the autistic population (Quintana et al 2012;Porges 2007) and that the brain, body and behavior components have to be addressed in order to achieve improvements in social cognition for children with ASD.…”
Section: Emotional Responsivenessmentioning
confidence: 99%
“…The scores for the total scale (M) and the subscales speech/language/communication (Com), sociability (Soc), sensory and cognitive awareness (Cog) and health/physical/behavior (Beh) are displayed for the preand posttest for Groups 1 and 2. The lower scores in the postcompared to the pre-test indicate treatment success the autonomic nervous system and social cognition is closely linked in the autistic population (Quintana et al 2012;Porges 2007) and that the brain, body and behavior components have to be addressed in order to achieve improvements in social cognition for children with ASD.…”
Section: Emotional Responsivenessmentioning
confidence: 99%
“…It has been suggested that vagal reactivity, otherwise known as vagal withdrawal, plays a role in emotional regulation (Porges, 2007), which is impaired in many children with oppositional defiant disorder (ODD) (Cavanagh, Quinn, Duncan, Graham, & Balbuena, 2017). However, results are inconsistent (Graziano & Derefinko, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Porges's Polyvagal Theory (Porges, 2007) asserts that engagement with the environment is physiologically mediated by the ventral vagal complex. Pathways originating in the nucleus ambiguous, which regulates vagal influence on the heart, are linked to those that regulate muscles controlling facial expressions and vocalizing.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for most people, caring and affiliative relationships are the most important sources of threat regulation (Cacioppo & Patrick, 2008). For the most part, threat and drive emotions stimulate the sympathetic nervous system, whereas soothing, calming and feeling safe are linked to the parasympathetic system, which in turn has a vast array of physiological and psychological effects (Porges, 2007). There is growing evidence that feeling socially safe, which is linked to parasympathetic activity, is a better predictor of vulnerability to psychopathology than 'excitement-based' positive emotion ) and a better predictor than general positive or negative affect and social support (Kelly, Zuroff, Leybman, & Gilbert, 2012).…”
Section: The Evolutionary Function Analysis Of Emotion Systemsmentioning
confidence: 99%
“…Physiologically, the community would constantly try to shift from sympathetic dominant to parasympathetic engagement (Porges, 2007). We predict that stimulation of the parasympathetic autonomic nervous system within social contexts requires discouragement of high expressed emotion and shaming experiences.…”
Section: The Evolutionary Function Analysis Of Emotion Systemsmentioning
confidence: 99%